2022
DOI: 10.3390/healthcare10030503
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists’ Knowledge, Willingness, and Readiness to Prescribe Oral Contraceptives in Saudi Arabia

Abstract: Background: The role of community pharmacists (CPs) in various healthcare settings is well documented in the literature including providing safe and easy access to medications. Oral contraceptives (OCPs) are the most frequently used method of terminating unwanted pregnancies worldwide. Objective: This study aims to evaluate the Community pharmacist’s knowledge, willingness, and readiness to prescribe OCPs in Saudi communities in Saudi Arabia. Methods: This is across sectional, self-administered questionnaire-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
3
2
Order By: Relevance
“…Previous studies have reported good knowledge among pharmacists [24,25]. In this study, there was no significant association between socio-demographics and additional degree in pharmacy or receiving of training on contraceptives on the participants' knowledge of oral contraceptives.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies have reported good knowledge among pharmacists [24,25]. In this study, there was no significant association between socio-demographics and additional degree in pharmacy or receiving of training on contraceptives on the participants' knowledge of oral contraceptives.…”
Section: Discussioncontrasting
confidence: 71%
“…In contrast to the study conducted by Liu et al in China, this study indicated that the study participants were willing to provide remote services to their patients [21]. Participants in a study done by Ahmed et al were shown to be less prepared for telepharmacy [22]. According to Elnaem et al, around 67% of the senior pharmacy students at a Malaysian public pharmacy school displayed excellent knowledge and 68% demonstrated high readiness.…”
Section: Discussioncontrasting
confidence: 58%
“…Continuing professional education and intense training may aid in increasing knowledge, which may improve community pharmacists' perception and willingness to practice. Te availability of appropriate and efcient resources, as well as the supply of incentives to pharmacists, would aid in the promotion of telepharmacy implementation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have discussed the knowledge and practice of medical doctors regarding acne management. Previous studies in Saudi Arabia among healthcare providers' reported low knowledge of acne management (1,12,13). Among those studies, a study by Khalid et al (12) examined the knowledge, attitudes, and practices of doctors working in primary health care centers about acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…Among those studies, a study by Khalid et al (12) examined the knowledge, attitudes, and practices of doctors working in primary health care centers about acne vulgaris. It was a cross-sectional study carried out in 30 PHCs in Riyadh in 2000 and involved 144 physicians (13). Inappropriate behavior and a lack of understanding among the health care professionals were the outcomes that were associated with lower knowledge of acne.…”
Section: Introductionmentioning
confidence: 99%